2021
DOI: 10.1016/j.marpetgeo.2020.104746
|View full text |Cite
|
Sign up to set email alerts
|

Effects of postglacial seawater intrusion on sediment geochemical characteristics in the Romanian sector of the Black Sea

Abstract: Pore water and sediment geochemistry in the western Black Sea were investigated on long Calypso piston core samples. Using this type of coring device facilitates the recovery of the thick sediment record necessary to analyze transport-reaction processes in response to the postglacial sea-level rise and intrusion of Mediterranean salt water 9 ka ago, and thus, to better characterize key biogeochemical processes and process changes in response to the shift from lacustrine to marine bottom water composition. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 100 publications
7
38
1
Order By: Relevance
“…1) a light-grey zone free of sediment, with white patches (A, Fig. 4, delineated by a white which is also a GH-rich zone where the brown color indicates the presence of iron-bearing minerals at an elevated concentration in the Black Sea (Egger et al, 2016), as also shown in a complementary study (Ruffine et al, 2021), 3) a dark-grey area with small white patches, which is a less rich GH-zone, at the bottom right-hand side (Fig. 4, C, delineated by a green dotted line) where solid hydrates (or ice) are intermixed with sediments.…”
Section: Raman Analysissupporting
confidence: 58%
See 4 more Smart Citations
“…1) a light-grey zone free of sediment, with white patches (A, Fig. 4, delineated by a white which is also a GH-rich zone where the brown color indicates the presence of iron-bearing minerals at an elevated concentration in the Black Sea (Egger et al, 2016), as also shown in a complementary study (Ruffine et al, 2021), 3) a dark-grey area with small white patches, which is a less rich GH-zone, at the bottom right-hand side (Fig. 4, C, delineated by a green dotted line) where solid hydrates (or ice) are intermixed with sediments.…”
Section: Raman Analysissupporting
confidence: 58%
“…However, previous studies have shown that the limnic sediment is characterized by a lower salinity (Ruffine et al, 2021;Soulet et al, 2010). Therefore, the seepage of brine is unlikely in the study area.…”
Section: 3a Spatial Variability Of the Guest's Distributionmentioning
confidence: 78%
See 3 more Smart Citations